Goals and Habits: Exploring Local Government Governance Models in China—A Comparative Analysis of COVID-19 Prevention Strategies and Their Psychological Impact on Sports and Community Engagement - Liang Yanrunyu; Guo Shengli (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The governance strategies employed by local governments in China reveal a tension between rigid policy objectives and the flexibility needed for effective implementation. While local governments often adopt "muddling through" approaches to navigate demanding policy objectives, the COVID-19 pandemic presented a unique challenge with its rigid and high-stakes prevention requirements. This study examines the contrasting approaches to COVID-19 prevention in selected Chinese cities, focusing on the psychological and social impacts of these governance models on community engagement, including sports and recreational activities. Using a task attribute and management habits framework, the study highlights how localized management habits influence epidemic prevention strategies. Cities with high specialization, autonomy, and strong coordination capabilities developed precise prevention models, balancing political and professional responsibilities. These models enabled more nuanced and community-sensitive responses, preserving opportunities for physical activity and social cohesion. Conversely, campaign-style prevention, characterized by rigid command structures and top-down directives, limited flexibility and often disrupted community activities, including sports and recreation. The findings emphasize the importance of integrating psychological and social considerations into governance strategies, particularly during crises. By fostering localized, professional, and coordinated approaches, governments can better support community well-being, including maintaining access to sports and recreational spaces, which are vital for physical and mental health during challenging times. This analysis provides valuable insights for sports psychology by exploring the interplay between governance models and their impact on community resilience and engagement.